Oropouche Fever, Cuba, May 2024 - Ana Julia Benitez; Mayling Alvarez; Lissette Perez; Rosario Gravier; Silvia Serrano; Denelsys Milagro Hernandez; Melissa Maria Perez; Gladys Gutierrez-Bugallo; Yanet Martinez; Ariamys Companioni; Carilda Peña; Jose Raul de Armas; et al. (Emerging Infectious Diseases)
Phylogenetic analyses showed that the virus responsible for a May 2024 Oropouche fever outbreak in Cuba was closely related to viruses from Brazil in 2023. Pools of Ceratopogonidae spp. biting midges and Culex quinquefasciatus mosquitoes were positive for Oropouche viral RNA. No cases were severe. Virus extension to new areas may increase case numbers and severity.